history book for Muhammad bin Adam Al-Baliki (d.1237 A.H.): Department (Life of Imam Muhammad bin Ali bin Musai - Muhammad Al-Jawad - {195-220 A.H}): study and Achievement - Dewane, Abubakir (Al-Adab Journal, 2021)
This study is entitled “The Biography of Imam Muhammad Ali, the Son of Moses Raza Known as, Muhammad Jawad (195-220 H) From the book of History by Muhammad Adam Balaky: An Investigation and Assertion”. The current study consists of two chapters. The first chapter, which is devoted to the investigation of the manuscript, is also divided into two sections. The first section includes a description of the manuscript and the methodology applied by the researcher with the purpose of asserting the manuscript as been written by the great scholar ‘Ibin Adam’. In fact, the part concerned with the life of his family and more specifically the biography of Imam Muhammad Ali, the son of Moses Raza, has been chosen as the topic for investigation and assertion. Therefore, his glory, biography and attitudes have been explained. The second section is concerned with the description of the approach and methodology applied by the great scholar ‘ Ibin Adam’ in his book. As far as the second chapter is concerned, it deals with asserting the manuscript starting from the manuscript plate number (422) up to manuscript number (424) with regard to the number of the manuscript because the page numbers are not clear enough to be read.